Ontological Consequences of the Ethics of Technology - Peter Kondrla; Primoz Repar (Communications - Scientific letters of the University of Zilina, 2017)
Development of new technologies is accompanied by a necessary ethical reflection of them. This ethical reflection, for the sake of the legitimization of its own discourse, defines the relations between the fundamental ontological categories such as human, culture, nature, technology and product. Ontological interpretation of these relations is bound to the specific model of rationality. This study compares two types of rationality for the interpretation of the relations between the concepts of man, nature, and the culture of technological developments and formulates the ontological consequences of both approaches. The first approach is the theory of Arne Naes, who in his theory departs from an anthropocentric starting point for understanding the relation between man and nature, preferring instead an understanding of the biosphere as a bearer of moral values [1]. The bearer of values is not in the human consciousness which makes the evaluation of objects and nature but the bearer is in the ecosystem and its autonomous existence. Bruno Latour, on the contrary, includes in the complexity of being not only human beings but also the products of technological processes, calling them hybrids or quasi-objects. The nature and quasi-object together constitute a sphere of transcendence. A comparison of the two approaches is focused on the definition of transcendence as a potential bearer of values, meanings and moral responsibility. We compare both approaches and evaluate the possibility of their use in the development of new concepts in ethics of technology.